Significance of Urinary Proteome Pattern in Renal Allograft Recipients - Sufi M. Suhail (Journal of Transplantation)
Urinary proteomics is developing as a platform of urinary biomarkers of immense potential in recent years. The definition of urinary proteome in the context of renal allograft and characterization of different proteome patterns in various graft dysfunctions have led to the development of a distinct science of this noninvasive tool. Substantial numbers of studies have shown that different renal allograft disease states, both acute and chronic, could portray unique urinary proteome pattern enabling early diagnosis of graft dysfunction and proper manipulation of immunosuppressive strategy that could impact graft prognosis. The methodology of the urinary proteome is nonetheless not more complex than that of other sophisticated assays of conventional urinary protein analysis. Moreover, the need for a centralized database is also felt by the researchers as more and more studies have been presenting their results from different corners and as systems of organizing these newly emerging data being developed at international and national levels. In this context concept of urinary proteomics in renal allograft recipients would be of significant importance in clinical transplantation.